(untitled) (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2024)
Satellite telemetry has transformed the study of marine megafauna movement ecology, enabling continuous tracking of large-bodied oceanic vertebrates across ocean basins, identifying critical foraging and breeding habitats, quantifying exposure to anthropogenic threats, and informing the spatial design of marine protected areas. This study presents a multi-species comparative analysis of satellite telemetry datasets from 847 tagged individuals across eight marine megafauna taxa – blue whale (Balaenoptera musculus), leatherback sea turtle (Dermochelys coriacea), whale shark (Rhincodon typus), great white shark (Carcharodon carcharias), loggerhead sea turtle (Caretta caretta), northern elephant seal (Mirounga angustirostris), wandering albatross (Diomedea exulans), and southern bluefin tuna (Thunnus maccoyii) – tracked over a cumulative 14,847 tracking days. Home range sizes (95% kernel utilisation distribution) ranged from 84,200 km2 (elephant seal foraging excursion) to 47.4 million km2 (wandering albatross annual range). Inter-individual movement consistency within species – quantified as the intraclass correlation of daily displacement distance – averaged 0.64 +- 0.18, indicating substantial but incomplete individual specialisation in space use. Anthropogenic threat hotspot analysis revealed that 68.4% of tracked blue whale core habitat (50% KUD) overlapped with high-intensity commercial shipping lanes, and 47.2% of leatherback turtle foraging areas overlapped with longline fishing effort exceeding 1,000 hooks/km2/year. Biological oceanographic drivers – sea surface temperature, chlorophyll-a concentration, and mixed layer depth – collectively explained 74.2% of variance in blue whale habitat use via habitat suitability modelling. These results highlight both the power of satellite telemetry for conservation-relevant spatial ecology and persistent data gaps requiring expanded tagging programmes in under-monitored ocean regions.